Established a business plan for Nawari Travel And Tours Sdn Bhd, Kuala Terengganu / Zaliha Bt. Zainuddin ... [et al.] - Zainuddin, Zaliha; Ali, Zaleha; Omar, Aida Nurbani; Ahmad, Rozita (2004)
World tourism industry scenario particularly of the East Asia Pacific show a positive growth and directly influence the tourism industry development and tourist arrivals in Malaysia. Globally, total international tourist arrival by region forecasted by Global Stats. Corp (1997) an annual growth rate between 5% - 7%. This is a good indicator for any tourism businesses that interrelated with tourism such as hoteliers, resort operator, airliners, travel operators and agencies, theme park operators etc.